DEGRADASI SENYAWA IMIDAKLOPRID SECARA ADVANCED OXIDATION PROCESSES DENGAN PENAMBAHAN TIO2-ANATASE - Amelia, Fitrah; -, Safni; Suyani, Hamzar (Universitas Andalas, 2015)
Imidacloprid is active compounds in Confidor 200 SL withÂ have toxical character. Degradation of Imidacloprid in Advanced Oxidation Processes (AOPs) method by using TiO2 catalyst can reduce toxic level. Advanced Oxidation Processes (AOPs) method which is used is Sonolysis, Photolysis, and Ozonolisis. The result of sonolysis, Photolysis, and Ozonolysis measured by spectrophotometer UV-Vis with Î» 400-600 nm, and than optimum degradation waste after addition of catalys measured by HPLC. The result of degradation of Imidacloprid 6 mg/L using sonolysis without addition catalys is more smallest from addition catalys which degradated in 60 minute, temperature 25Â±1 Â°C. At the same time with Photolysis methode for addition catalys we get the degradation is more biggest from addition catalys. Degradation percentage of imidacloprid without addition of TiO2-anatase reach is small from with addition of TiO2. Measure using HPLC for each methode we get more than one peak in chromatogram. It means there are other coumpounds in imidacloprid solution.